La tierra entre derecho y cultura indígena en Argentina (Altre Modernità, 2009)
The paper considers the relationships between the indigenous peoples and the Argentinian State since the XIX century until 1994, when it was introduced in the Constitution the provision acknowledging to the indigenous peoples “la posesión y propiedad comunitarias de las tierras que tradicionalmente ocupan”, “la entrega de otras aptas y suficientes para el desarrollo humano” and granting them “la parcipación en la gestión referida a sus recursos naturales y a los demás intereses que los afecten” (art. 75, inc. 17). The paper describes then the issue concerning the claim for indigenous land – raised by the new constitutional provision – and focuses on some significant cases and the more recent jurisprudence on that issue.